ON THE INEQUALITIES CONCERNING POLYNOMIAL-EXPONENTIAL BOUNDS FOR INVERSE TRIGONOMETRIC FUNCTION - Ramkrishna M. Dhaigude; Sumedh B. Thool; Rupesh R. Atram (International Journal of Innovations in Engineering Research and Technology, 2024)
Recent research works on mathematical inequalities shows the importance bounds of polynomial-exponential type for various functions.